2009
DOI: 10.1016/j.otohns.2009.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the External Jugular Venous Drainage System in Neck Dissection

Abstract: EJV preservation may reduce immediate postoperative neck edema and pain/discomfort related to neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
5
0
7
Order By: Relevance
“…In the literature, the effects of ND on CCA and IJV have been discussed [19][20][21]. There are also studies about the patency of IJV in ND [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the effects of ND on CCA and IJV have been discussed [19][20][21]. There are also studies about the patency of IJV in ND [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the external jugular vein (EJV) was sacrificed because the authors believed that the venous drainage was sufficient owing to the unilateral IJV preservation. However, Chung et al 19 concluded that EJV preservation could help decrease the immediate postoperative neck edema related to neck dissection. Preservation of the EJV might be recommended for a bilateral neck dissection, even if a unilateral IJV is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…[2] A number of anatomical variations of the external jugular vein are found either in its formation, course, tributaries or termination. [3] Clinically the external jugular vein is approached for the cannulation, [4] surgical central venous pressure measurement and various radiological procedures. [5] So any variations in the formation, course and drainage of the external jugular vein can influence the outcome of the surgeons, clinical and radiologists.…”
Section: Introductionmentioning
confidence: 99%